Synthesis and Study of New Quinolineaminoethanols as Anti-Bacterial Drugs - Pierre Laumaillé; Alexandra Dassonville-Klimpt; François Peltier; Catherine Mullié; Claire Andréjak; Sophie Da-Nascimento; Sandrine Castelain; Pascal Sonnet (MDPI AG, 2019)
The lack of antibiotics with a novel mode of action associated with the spread of drug resistant bacteria make the fight against infectious diseases particularly challenging. A quinoline core is found in several anti-infectious drugs, such as mefloquine and bedaquiline. Two main objectives were set in this work. Firstly, we evaluated the anti-mycobacterial properties of the previous quinolines 3, which have been identified as good candidates against ESKAPEE (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, Enterobacter spp. and Escherichia coli) bacteria. Secondly, a new series 4 was designed and assessed against the same bacteria strains, taking the pair of enantiomers 3m/3n as the lead. More than twenty compounds 4 were prepared through a five-step asymmetric synthesis with good enantiomeric excesses (>90%). Interestingly, all compounds of series 3 were efficient on M. avium with MIC = 2−16 µg/mL, while series 4 was less active. Both series 3 and 4 were generally more active than mefloquine against the ESKAPEE bacteria. The quinolines 4 were either active against Gram-positive bacteria (MIC ≤ 4 µg/mL for 4c−4h and 4k/4l) or E. coli (MIC = 32−64 µg/mL for 4q−4v) according to the global lipophilicity of these compounds.